Peripheral blood blast rate of clearance is an independent predictor of clinical response and outcomes in acute myeloid leukaemia. (5th December 2019) - Holtzman, Noa G.; El Chaer, Firas; Baer, Maria R.; Ali, Omer; Patel, Ameet; Duong, Vu H.; Sausville, Edward A.; Singh, Zeba N.; Koka, Rima; Zou, Ying S.; Etemadi, Arash; Emadi, Ashkan
Summary: The day 14 bone marrow aspirate and biopsy (D14BM) is regularly used to predict achievement of complete remission (CR) with induction chemotherapy in acute myeloid leukemia (AML), however its utility has been questioned. Clearance of peripheral blood blasts (PBB) may serve as an early measure of chemosensitivity. PBB rate of clearance (PBB‐RC) was calculated for treatment‐naive AML patients ( n  = 164) undergoing induction with an anthracycline and cytarabine (7+3) and with detectable PBB at diagnosis. PBB‐RC was defined as the percentage of the absolute PBB count on the day of diagnosis that was cleared with each day of therapy, on average, until D14 or day of PBB clearance. Each 5% increase in PBB‐RC approximately doubled the likelihood of D14BM clearance (OR = 1·81; 95% CI: 1·24–2·64, P  < 0·005). PBB‐RC was also associated with improved CR rates (OR per 5% = 1·97; 95% CI: 1·27–3·01, P  < 0·005) and overall survival (OS) [hazard ratio (HR) per 5% = 0·67; 95% CI: 0·52–0·87]. African American patients had poorer OS adjusted for PBB‐RC (HR = 2·18; 95% CI: 1·13–4·23), while race was not associated with D14BM or CR rate. PBB‐RC during induction chemotherapy is predictive of D14BM clearance, CR, and OS, and can therefore serve as a prognostic marker for clinical outcomes in AML.